ANALISIS KESULITAN SISWA SMP DALAM MENGERJAKAN SOAL MATERI LINGKARAN DITINJAU DARI ASPEK VISUALISASI - Nasution, Eline Yanty Putri; Nurhaliza, Ema; Rusliah, Nur (Nabla Dewantara: Jurnal Pendidikan Matematika, 2025)
The mathematical component consists of numbers and abstract symbols which often become difficulties for students in understanding a geometric element. This affects the ability of students to work on math problems. Therefore, it is necessary to apply good learning so that students are able to solve problems, especially in mathematics. The purpose of this study was to analyze students' difficulties in working on circle material problems in terms of the visualization aspect and its influence on learning mathematics. The research process was carried out in one of the public schools, namely State Junior High School 6 Sungai Penuh City. Sampling in this study was carried out by means of the Non Probability Sampling technique which is more precisely used by the author namely Purposive Sampling, namely sampling with a certain consideration, with the final result indicating the level of student difficulty and the level of student visualization. The results showed that 5 students had a high visualization level, 8 students had a moderate visualization level, and 9 students had a low visualization level. From the results it was found that the average difficulty factor experienced by students was the ability of students to understand concepts, solve verbal problems, describe sketches/drawings and errors in the algorithm process.